Performance and carcass characteristics of Santa Inês lambs fed different protein sources - Araújo, Tiago Gonçalves Pereira; Furtado, Dermeval Araújo; Miranda, Jaciara Ribeiro; Marques, Carlo Aldrovandi Torreão; Lisboa, Ana Cristina Chacon; Suassuna, Alberto; Medeiros, Ariosvaldo Nunes de (Acta Scientiarum. Animal Sciences, 2022)
The objective of this study was to evaluate the productive performance and carcass characteristics of confined Santa Inês sheep, fed different diets, in a Semiarid environment. Twenty whole sheep with 5 ± 0.5 months of age and 27 ± 2.0 kg were used, receiving two different diets for 72 experimental days, one composed of defatted soybean meal and the other of protein-enriched cactus meal. They were evaluated for different diets, consumption, production, carcass characteristics, morphometric measures and edible components. The experimental design was in randomized blocks with two treatments and 10 replications. Performance data and carcass characteristics were evaluated by analysis of variance and means compared by t test at 5% probability level using Statistical Analysis System [SAS]® (1999). Thus, the use of emulsified palm forage protein in the feeding of Santa Inês male lambs proved to be an excellent protein source when compared to the use of defatted soybean meal, since the results of performance and carcass characteristics were similar, being the use of this alternative source advised as it presents the best benefit-cost ratio.